2019
DOI: 10.1148/radiol.2019181714
|View full text |Cite
|
Sign up to set email alerts
|

Airway Microstructure in Idiopathic Pulmonary Fibrosis: Assessment at Hyperpolarized 3He Diffusion-weighted MRI

Abstract: This is a repository copy of Airway microstructure in idiopathic pulmonary fibrosis: assessment at hyperpolarized 3He diffusion-weighted MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 25 publications
5
47
0
Order By: Relevance
“…Previous studies have shown that 3 He and 129 Xe ADC is highly repeatable in COPD patients with a coefficient of variation of 2.98% and 2.77% respectively, over 5 visits 32 . Similarly it has been showed that 3 He Lm D in patients with idiopathic pulmonary fibrosis is highly repeatable with a 0.6% difference between same-day visits 20 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies have shown that 3 He and 129 Xe ADC is highly repeatable in COPD patients with a coefficient of variation of 2.98% and 2.77% respectively, over 5 visits 32 . Similarly it has been showed that 3 He Lm D in patients with idiopathic pulmonary fibrosis is highly repeatable with a 0.6% difference between same-day visits 20 .…”
Section: Discussionmentioning
confidence: 76%
“…These in vivo distal airspace measurements from hyperpolarised gas DW-MRI have shown good agreement with direct morphometric measurements in validation studies with lung specimens 8,10,11 . Numerous studies have used hyperpolarised gas DW-MRI to elucidate changes in distal airspaces related to smoking [12][13][14] , ageing 15 , lung inflation 16 , and diseases such as COPD 17,18 , asthma 19 , and idiopathic pulmonary fibrosis (IPF) 20 . However, due to the high cost and complex infrastructure required for hyperpolarised gas MRI, the technique is not typically employed in standard pulmonary function testing or screening for pulmonary disease.…”
mentioning
confidence: 99%
“…More specifically, previous studies have shown that hyperpolarised gas diffusion-weighted (DW) MRI provides a noninvasive, quantitative assessment of microstructural acinar changes in the lung [ 38 ]. However, the utility of 129-xenon diffusion imaging has not been studied previously in ILDs; it was evaluated in a prospective, multicentre trial for the first time and presented at the congress.…”
Section: Group 1402: Imagingmentioning
confidence: 99%
“…Chan et al (7) found that 3 He DW MRI depicted changes in IPF over time. In particular, global mean diffusion length increased at 12 months in the base and periphery of the lungs, whereas pulmonary function tests did not demonstrate any significant change.…”
mentioning
confidence: 99%
“…In conclusion, hyperpolarized gas MRI has proven to be to be a useful research tool that provides unique functional and structural information about the lungs and new insights into a variety of lung diseases. The study by Chan et al (7) demonstrates that 3 He DW MRI can provide global and regional assessment of the extent and severity of disease in patients with IPF, and excellent longitudinal assessment. 3 He DW MRI has the potential to become a sensitive outcome measure to depict, or even help predict, response to therapy sensitively and noninvasively.…”
mentioning
confidence: 99%